Medical Complications Predict Cognitive Decline in Nondemented Hip Fracture Patients—Results of a Prospective Observational Study. (March 2018) - Hack, Juliana; Eschbach, Daphne; Aigner, Rene; Oberkircher, Ludwig; Ruchholtz, Steffen; Bliemel, Christopher; Buecking, Benjamin
Objective: The aim of this study was to identify factors that are associated with cognitive decline in the long-term follow-up after hip fractures in previously nondemented patients. Methods: A consecutive series of 402 patients with hip fractures admitted to our university hospital were analyzed. After exclusion of all patients with preexisting dementia, 266 patients were included, of which 188 could be examined 6 months after surgery. Additional to several demographic data, cognitive ability was assessed using the Mini-Mental State Examination (MMSE). Patients with 19 or less points on the MMSE were considered demented. Furthermore, geriatric scores were recorded, as well as perioperative medical complications. Mini-Mental State Examination was performed again 6 months after surgery. Results: Of 188 previously nondemented patients, 12 (6.4%) patients showed a cognitive decline during the 6 months of follow-up. Multivariate regression analysis showed that age ( P = .040) and medical complications ( P = .048) were the only significant independent influencing factors for cognitive decline. Conclusions: In our patient population, the incidence of dementia exceeded the average age-appropriate cognitive decline. Significant independent influencing factors for cognitive decline were age and medical complications.